Public management and governance - Bovaird, A. G.; Löffler, Elke. (London ; New York : Routledge, 2009)
This book has been written with the aim of giving readers a clear picture of the current state of play and the most important emerging issues in public management and governance.
Includes bibliographical references (p. 343-362) and index.
aug 05/06/13
Loans
Keywords: Public administration; Government productivity; Legitimacy of governments; Public administration - citizen participation